Internet jako instrument strategii marketingowej banku - Grzegorczyk, Wojciech (Internet as an Instrument of Marketing Strategy of a Bank, 2005)
Investing by banks in new technology is a necessity nowadays, however, the raising of efficiency
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 63-71